Low Power MoS2/Nb2O5 Memtransistor Device with Highly Reliable Heterosynaptic Plasticity (Adv. Funct. Mater. 40/2021). (1st October 2021) - Nam, Jae Hyeon; Oh, Seyoung; Jang, Hye Yeon; Kwon, Ojun; Park, Heejeong; Park, Woojin; Kwon, Jung‐Dae; Kim, Yonghun; Cho, Byungjin
Abstract : Heterosynaptic Plasticity In article number 2104174, Jung‐Dae Kwon, Yonghun Kim, Byungjin Cho, and co‐workers demonstrate a highly reliable 2D MoS2 /Nb2 O5 memtransistor device based on Schottky barrier modulation is demonstrated. The 2D/oxide memtransistor attains dual‐terminal stimulated heterosynaptic plasticity, showing an extremely low power consumption of ≈6 pJ and reliable endurance characteristics over 2000 pulses. Finally, a high pattern recognition accuracy of ≈94.2% is achieved using a pattern recognition simulation, which promotes advanced neuromorphic systems.